When the eternal can be met : the Bergsonian theology of time in the works of C.S. Lewis, T.S. Eliot and W.H. Auden /: the Bergsonian theology of time in the works of C.S. Lewis, T.S. Eliot and W.H. Auden. (2014) - Latta, Corey
No abstract available